Designing Improvements to the Product Attributes of Sling Bags Based on Consumer Preferences Using the Conjoint Analysis Method - Brandon Dwinata Tjiandra; Boby Hera Sagita; Amelia Kurniawati (School of Industrial and System Engineering, Telkom University, 2023)
The Covid-19 pandemic, which ended in early 2023, has increased people's needs and provided newopportunities for businesses in the clothing/fashion sector. The object of this research is a company thatoffers various bag products such as backpacks, sling bags, hand bags and others. However, one of thecompany's product categories, namely sling bags, experienced a decline in sales during 2022. Thecompetition of companies engaged in clothing/fashion makes the company have to maintain its business.The purpose of this research is to design improvements to sling bag product attributes based on consumerpreferences. The Conjoint Analysis method is used to determine consumer preferences for sling bag productattributes so as to improve purchasing decisions and retain company customers. The number of samples usedwas 93 respondents with the majority of students aged 18-35 years. The final results of the study are themost important attributes and attribute level utility values, namely neutral color attributes (black, gray,white), price attributes IDR 80,000-Rp160,000, small size attributes 2.3 L (24 x 16 x 6 cm), canvas materialattributes, hobo bag model attributes, and feature attributes, namely 3-4 partitions, waterproof, andpermanent straps. The results of the study can be used to provide an overview of the company's consumerpreferences in sling bag products and can be a consideration for companies in releasing new products.